COLLECTION DEVELOPMENT POLICIES OF ARTS AND SCIENCE COLLEGES AFFILIATED TO CALICUT UNIVERSITY, KERALA-A STUDY - JESMI, P.J (Asian Journal of Educational Research, 2015)
This study is focused on the collection development policy in college libraries. It was conducted in arts and science colleges. Collection development remains a corner stone responsibility in academic and research libraries. A policy can be unwritten convention or a written document. The guidelines should be formulated keeping in mind the aims and objectives of the library and the current and future needs of its users. The policy statement should cover information /documents in all the subjects’ field in a variety of formats. It implies that collection development policies are significantly changing, and libraries need to disseminate widely information on their collection policies. Collection development is a dynamic and continuous activity. It involves the users, the library staff, and the subject experts on selection team. It is not an end in itself, but a means to develop a need-based, up to-date, and balanced collection fit to meet the document and information needs of the users. Most library collection development policy statements include a description of user needs; an overview of what is collected to meet those needs; who on the library staff collects what; and a very detailed subject breakdown of what is regularly added to the collection. The collection development policy is a planning document produced by the library which identifies and communicates the long and short term collection goals and policies of the library system. Collection development policies also function as a guide to library resources for faculty, other users, and other libraries by describing the scope and nature of the collection. As an indication of collection strength and weakness, they can be useful in resource sharing and cooperative acquisitions. A well framed collection development policy is of a great help in developing a good collection.